Pengaruh Model Pembelajaran Core pada Materi Pelestarian Flora dan Fauna terhadap hasil Belajar Siswa - Toni Hardianto; Aditya Akbar Saputra; Bayu Kurniaaji; Bambang Darmawan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This study aims to determine whether there is an effect of Core learning model on flora and fauna conservation material on student learning outcomes. This research uses a quantitative and descriptive design that involves data processing in the form of pre-test and post-test. Classroom Action Research (PTK) aims to improve learning outcomes and improve learning practices in the classroom more professionally at SMA Negeri 1 Sukoharjo. F-6 phase students totaling 31 students in the first semester of SMA Negeri 1 Sukoharjo in the 2023/2024 academic year. Whether or not there is an influence of student learning activities, teacher teaching activities and student Geography learning outcomes taught using the CORE type cooperative learning model. Research data were obtained from observation sheets and learning outcomes tests. Based on the analysis results obtained that: 1) on the pre-test worksheet the average number of students who have not completed is 45.16% and on the post-test worksheet the number of students who have not completed is 3.2% which is categorized as increased; 2) There was an increase in Geography learning outcomes of phase F-6 students of SMA Negeri 1 Sukoharjo from the pre-test worksheet to the post-test worksheet. The pre-test worksheet showed that 17 students scored ≥ 75 with an average score of 84.5 which was categorized as good. Furthermore, the results of the post-test worksheet showed a significant increase because there were 30 students who scored ≥75 with an average score of 95.5 which was categorized as excellent.